1995
DOI: 10.1111/j.1472-8206.1995.tb00525.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety of nitrofurantoin during the first trimester of pregnancy: meta‐analysis

Abstract: Asymptomatic bacteriuria is common during pregnancy and may adversely affect both the mother and her fetus. Nitrofurantoin (NF) has been long recognized as an effective agent in both nonpregnant and pregnant women suffering from urinary tract infections. This meta-analysis was conducted in order to evaluate the safety of NF ingested during early pregnancy. Of twenty-two studies, only four met the inclusion criteria and their analysis could not demonstrate any significant correlation between NF ingestion and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Investigations have shown that addition of folic acid may prevent neural tube defects and urinary tract defects [21,22]. Other antimicrobial drugs used for urinary tract infection such as nitrofurantoin were not associated with either urinary tract or other defects [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have shown that addition of folic acid may prevent neural tube defects and urinary tract defects [21,22]. Other antimicrobial drugs used for urinary tract infection such as nitrofurantoin were not associated with either urinary tract or other defects [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 11, 2018 dmd.aspetjournals.org Downloaded from studies have not shown side effects of fetal exposure of this drug (Prytherch et al, 1984), and human studies with a relatively small amount of data did not show evidence of harmful effects of NFT to the fetus Ben David et al, 1995), adverse effects related to the fetal exposure of NFT have recently been suggested. For example, there is evidence that links craniosynostosis to fetal exposure to NFT and drugs with similar chemical structures (Gardner et al, 1998;Källén and Robert-Gnansia, 2005).…”
Section: Bcrp and Fetal Distribution Of Nitrofurantoinmentioning
confidence: 99%
“…The authors concluded because of the lack of good quality primary data and appropriate sample size, and therefore power, it is not possible to draw reliable conclusions on what is the best class, route or regimen of antibiotics to treat symptomatic urinary tract infections during pregnancy. One meta-analysis of four trials reported a non significant pooled odds ratio of any fetal malformation with nitrofurantoin of 1·29 (95% CI 0·25-6·57), although the number and quality of the studies included are limited [80]. There is a low level of resistance to nitrofurantoin among uropathogens with NCCLS data from 2000 reporting only a rate of 1% [81].…”
Section: Treatmentmentioning
confidence: 99%